2011
DOI: 10.1111/j.1476-5381.2011.01517.x
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil restores cognitive function without affecting β-amyloid burden in a mouse model of Alzheimer's disease

Abstract: BACKGROUND AND PURPOSE Inhibitors of phosphodiesterase 5 (PDE5) affect signalling pathways by elevating cGMP, which is a second messenger involved in processes of neuroplasticity. In the present study, the effects of the PDE5 inhibitor, sildenafil, on the pathological features of Alzheimer's disease and on memory‐related behaviour were investigated. EXPERIMENTAL APPROACH Sildenafil was administered to the Tg2576 transgenic mouse model of Alzheimer's disease and to age‐matched negative littermates (controls). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
138
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(146 citation statements)
references
References 77 publications
(97 reference statements)
8
138
0
Order By: Relevance
“…Finally, the inhibition of HDAC6 may facilitate the degradation of misfolded proteins, such as Aβ and pTau (Sung et al, 2012;Yu et al, 2013;Zhang et al, 2014). Although different studies have demonstrated that HDACi or PDE5i improved cognitive deficits in animal models of AD, their role on amyloid pathology is controversial (Benito et al, 2015;Cuadrado-Tejedor et al, 2011b;Garcia-Barroso et al, 2013;Puzzo et al, 2009;Qing et al, 2008;Ricobaraza et al, 2009;Rumbaugh et al, 2015;Zhang and Schluesener, 2013). These differences may be because of the selectivity and potency of each compound and the different animal models and treatments employed.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Finally, the inhibition of HDAC6 may facilitate the degradation of misfolded proteins, such as Aβ and pTau (Sung et al, 2012;Yu et al, 2013;Zhang et al, 2014). Although different studies have demonstrated that HDACi or PDE5i improved cognitive deficits in animal models of AD, their role on amyloid pathology is controversial (Benito et al, 2015;Cuadrado-Tejedor et al, 2011b;Garcia-Barroso et al, 2013;Puzzo et al, 2009;Qing et al, 2008;Ricobaraza et al, 2009;Rumbaugh et al, 2015;Zhang and Schluesener, 2013). These differences may be because of the selectivity and potency of each compound and the different animal models and treatments employed.…”
Section: Discussionmentioning
confidence: 85%
“…By inhibiting PDE5, CM-414 can restore memory through the activation of the cGMP/CREB pathway that plays an important role in synaptic plasticity (Lu and Hawkins, 2002;Lu et al, 1999). Furthermore, the inhibition of PDE5 might diminish tau phosphorylation by favoring the inactive form of GSK3β (GSK3β-Ser9) (Cuadrado-Tejedor et al, 2011b;GarciaBarroso et al, 2013). On the other hand, through the inhibition of HDAC class I in conjunction with CREB activation, CM-414 may also facilitate the transcription of more specific memory-related genes, thereby reducing the indiscriminate transcription provoked by other HDAC class I inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Puzzo et al [130] first demonstrated the preclinical efficacy of PDE5 inhibitors in AD mouse models and the findings were later confirmed by other groups [131][132][133]. Among reported PDE5 inhibitors, tadalafil and sildenafil can penetrate into the brain and ameliorate synaptic, learning, and memory deficits by modulating the cyclic guanosine monophosphate intracellular signaling pathway [130,134].…”
Section: Phosphodiesterase 5 Inhibitorsmentioning
confidence: 89%
“…97 In AD mouse models, cGMP-dependent inactivation of GSK3β by PDE5 inhibitors leads to a decrease in hyperphosphorylated tau in the brain areas involved in learning and memory. 30,32 As tau phosphorylation better correlates with cognitive impairment in AD than amyloid burden, 133 increased hippocampal pAkt and pGSK3β-Ser9 levels have been proposed to underlie the improvements in learning and memory consolidation observed in sildenafil-and tadalafil-treated AD mice. 30,32 Similar activation of the Akt pathway by tadalafil has been proposed to increase cell survival in different peripheral tissues.…”
Section: +mentioning
confidence: 99%
“…30,32 As tau phosphorylation better correlates with cognitive impairment in AD than amyloid burden, 133 increased hippocampal pAkt and pGSK3β-Ser9 levels have been proposed to underlie the improvements in learning and memory consolidation observed in sildenafil-and tadalafil-treated AD mice. 30,32 Similar activation of the Akt pathway by tadalafil has been proposed to increase cell survival in different peripheral tissues. 134,135 This association between NO-cGMP signaling and tau phosphorylation via pGSK3β activity is supported by the existence of a signaling cascade that links cGMP activation with GSK3 inhibition.…”
Section: +mentioning
confidence: 99%